2011
DOI: 10.1007/s10522-011-9345-4
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of attenuation of pro-inflammatory Ang II-induced NF-κB activation by genistein in the kidneys of male rats during aging

Abstract: Angiotensin II (Ang II), a main effector of the renin-angiotensin system, is recognized as a pro-inflammatory mediator on age-related vascular inflammation. Ang II is one of the most important oxidative stress inducer, activates the redox-sensitive transcription factor, nuclear factor-κB (NF-κB) during aging. Genistein, a major component found in isoflavone, has anti-inflammatory activities that are often associated with its anti-oxidative activity. The purpose of this study is to document molecular mechanism … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
12
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 46 publications
2
12
0
Order By: Relevance
“…The AT1R is the main target receptor of Ang II and it plays a key role in blood pressure regulation, vasoconstriction and oxidative stress [1012], whereas the AT2R typically plays an opposing, protective role in such responses [1315]. We confirmed that renal AT1R expression is increased in old age [3, 16] – a known effect of the actions of IL-1β and TNF-α [17] – both of which were also upregulated here. Moreover, there was a profound reduction in vascular AT2R expression during aging such that the ratio of AT1R/AT2R expression was markedly increased in mesenteric arteries, providing a plausible mechanism for the markedly augmented pressor and contractile responses to infusion of low-dose Ang II.…”
Section: Discussionsupporting
confidence: 66%
“…The AT1R is the main target receptor of Ang II and it plays a key role in blood pressure regulation, vasoconstriction and oxidative stress [1012], whereas the AT2R typically plays an opposing, protective role in such responses [1315]. We confirmed that renal AT1R expression is increased in old age [3, 16] – a known effect of the actions of IL-1β and TNF-α [17] – both of which were also upregulated here. Moreover, there was a profound reduction in vascular AT2R expression during aging such that the ratio of AT1R/AT2R expression was markedly increased in mesenteric arteries, providing a plausible mechanism for the markedly augmented pressor and contractile responses to infusion of low-dose Ang II.…”
Section: Discussionsupporting
confidence: 66%
“…We found that injection of Aβ 1–40 into the rat brain was associated with astrocytic hypertrophy and this event was significantly inhibited by genistein. Previous studies have demonstrated that genistein has an anti-inflammatory impact on conditions such as diabetes [18] and on various types of tissue, including retina [19], gut [20], respiratory organs [21], kidney [22], and arthritic joints [23,24]. Genistein exerts its anti-inflammatory effect by influencing transcription factors, enzymes, and inflammatory mediators that are involved in inducing inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…The RAS in the CNS may contribute to the disease process of CNS disorders including AD, probably through neuronal death and memory dysfunctions. 9,56,57 High levels of angiotensin II are reported to contribute to oxidative stress 58 and inflammation 59 which produce deleterious effects in the CNS. It has been noted that ACEIs may provide benefits in cognition beyond blood pressure control.…”
Section: Discussionmentioning
confidence: 99%